The Compounding Processs of Bahasa Banjar (An Initiation towards Learning Bahasa Banjar as Local Content) - Ida Rusdiana; Nana Suciati*; Syahbuddin Syahbuddin (Universitas Syiah Kuala, 2023)
This study aims to describe the compounding process in Bahasa Banjar in its basic forms based on word classes. The research design is in the form of qualitative descriptive. The data used is in the form of primary data, namely native speakers and secondary data, namely documents related to the compounding of bahasa Banjar such as research results, books, and dictionaries. Data was collected from interview. The data analysis procedure was carried out through three flows of activities that occurred simultaneously, following the concept put forward by (Miles et al., 2014): data reduction, data presentation, and conclusions/verification. In this study triangulation of data sources and peer checking (Flick, 2009) was applied to check the validity of the data. Based on the word classes which form compounds in Bahasa Banjar, it can be concluded ten forms. Those are 1) Noun+Noun, 2) Noun+Verb, 3) Noun+Adjective, 4) Noun+Numeral, 5) Noun+Pronoun, 6) Verb+Noun, 7) Verb+Verb, 8) Verbs+Adjectives, 9) Adjective+Noun, 10) Adjective+Adjective. Some compound morpheme functions can change word class and some cannot change word class. The meanings of compound morphemes can be different from its constituent elements and can be related to the constituent elements.